Comparison of mifepristone plus misoprostol with misoprostol alone for first trimester medical abortion: A systematic review and meta-analysis - Shimels, Tariku; Getnet, Melsew; Shafie, Mensur; Belay, Lemi (Frontiers in Global Women's Health, 2023)
Objective: To compare mifepristone plus misoprostol combined regimen with misoprostol alone in medical abortion of first trimester pregnancy. Methods: Internet-based search of related literature was performed using text words contained in titles and abstracts. PubMed/Medline, Cochrane CENTRAL, EMBASE and Google scholar were used to locate English-based articles published until December 2021.Studies fulfilling the inclusion criteria were selected, appraised and assessed for methodological quality. Included studies were pooled for meta-analysis, and results were presented in risk ratio at a 95% confidence interval. Findings: Nine studies comprising 2052 participants (1035 intervention and 1017 controls) were considered. Primary endpoints were complete expulsion, incomplete expulsion, missed abortion, and ongoing pregnancy. The intervention was found to more likely induce complete expulsion irrespective of gestational age (RR: 1.19; 95% C.I: 1.14-1.25). Administration of misoprostol 800mcg after 24 hours of mifepristone pre-treatment in the intervention group more likely induced complete expulsion (RR: 1.23; 95%C.I: 1.17-1.30) than after 48 hours. The intervention group was also more likely to experience complete expulsion when misoprostol was used either vaginally (RR: 1.16; 95% CI: 1.09-1.17), or buccal (RR: 1.23; 95%C.I: 1.16-1.30). The intervention is more effective among the subgroup with negative foetal heartbeat to reducing incomplete abortion (RR: 0.45;95%C.I: 0.26-0.78) compared to controls. Likely, the intervention more likely reduced both missed abortion (RR: 0.21; 95%C.I:0.08-0.91), and ongoing pregnancy (RR: 0.12; 95%C.I: 0.05-0.26). Fever was less likely to be reported (RR: 0.78; 95%C.I:0.12-0.89) whereas, subjective experience of bleeding was more likely to be encountered (RR: 1.31; 95%C.I: 1.13-1.53) by the intervention group. Conclusion: The review strengthened that the combined mifepristone and misoprostol regimen can be an effective medical management for inducing abortions during first trimester pregnancy in all contexts. Specially, there is a high level certainty of evidence on complete expulsion during the early stage, and its ability to reduce both missed and ongoing pregnancies.